Pre-operative serum total bilirubin level as an indicator marker of perforated appendicitis. - Kassim, Nur Karyatee; Jelani, Aniza M; T Ismail, T Salwani; Omar, Julia; Ibrahim, Hanim A; W Azman, W Norlina; Shafii, Noorazliyana; Yaacob, Najib Majdi (Bangladesh Journal of Medical Science, 2019)
Objectives: Acute appendicitis is one of the most common surgical emergencies. Perforated appendicitis can result in increased morbidity and mortality. Thus, early identification of perforation can reduce the impact on patient and improve outcome. Apart from total white cell count (TWCC), serum total bilirubin (SB) has been shown to indicate perforation in appendicitis. The aim of this study was to assess the usefulness of serum total bilirubin (SB) as the preoperative indicator for perforated appendicitis. Materials and Methods: This was a retrospective study of all appendicectomies cases done in Hospital Universiti Sains Malaysia (HUSM) over a one-year period in 2014. Only patients with histopathologically confirmed appendicitis with available liver function tests and total white blood cell count preoperatively were included in the study. These appendicitis cases were further divided into perforated and non-perforated based on histopathological reports obtained. Results: A total of 245 patients had appendicectomy done in 2014 between January to December 2014. Out of 110 from these 245 patients met the inclusion and exclusion criteria. SB was significantly higher (p<0.001) in patients with perforated appendix compared to non-perforated. Conclusion: In conclusion, this study showed that preoperative SB is a useful laboratory parameter for perforated appendicitis to improve clinical decision-making by the clinician. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.233-237